2024
DOI: 10.1101/2024.02.18.580859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single E205D allele of a key P450CYP6P3is driving metabolic pyrethroid resistance in the major African malaria vectorAnopheles gambiae

Jonas A. Kengne-Ouafo,
Mersimine Kouamo,
Abdullahi Muhammad
et al.

Abstract: Deciphering the molecular drivers of insecticide resistance is paramount to extend the effectiveness of malaria vector control tools. Here, we demonstrated that the E205D amino acid change in a key metabolic resistance P450CYP6P3drives pyrethroid resistance in the major malaria vector,Anopheles gambiae. Spatio-temporal whole genome Poolseq analyses in Cameroon detected a major P450-linked locus on chromosome 2R beside the sodium channel locus.In vitrometabolism assays with recombinantly expressedCYP6P3protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…While a CNV was found in the cluster, it did not include Cyp6aa1 and was not associated with resistance to deltamethrin. In Cameroon, a non-CNV haplotype has been shown to be associated with pyrethroid resistance (Kengne-Ouafo et al, 2024), while two large signals of selection are found around the same gene cluster, in the absence of any CNVs ( Anopheles gambiae 1000 Genomes Consortium et al, 2017). While these haplotypes have not yet been phenotypically tested, we believe it very likely that it is associated with deltamethrin resistance, given the consistent results coming out of our study and the wider literature.…”
Section: Discussionmentioning
confidence: 99%
“…While a CNV was found in the cluster, it did not include Cyp6aa1 and was not associated with resistance to deltamethrin. In Cameroon, a non-CNV haplotype has been shown to be associated with pyrethroid resistance (Kengne-Ouafo et al, 2024), while two large signals of selection are found around the same gene cluster, in the absence of any CNVs ( Anopheles gambiae 1000 Genomes Consortium et al, 2017). While these haplotypes have not yet been phenotypically tested, we believe it very likely that it is associated with deltamethrin resistance, given the consistent results coming out of our study and the wider literature.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, whole-genome sequencing combined with population genetics has revealed the full extent of positive selection acting upon the wild genomes of Anopheles populations ( Miles et al 2017 ; Clarkson et al 2020 ). These data have revealed a complex genetic architecture of insecticide resistance, including the involvement of amino acid mutations, copy number variants (CNVs), and cis-regulatory variation ( Lucas et al 2019 ; Clarkson et al 2021 ; Dyer et al 2023 ; Lucas et al 2023 ; Kengne-Ouafo et al 2024 ).…”
Section: Introductionmentioning
confidence: 99%